Pendampingan Pengenalan Penulisan Huruf Hijaiyah Melalui Media Kartu Di TPA Nurul Ihsan Kalampangan - Siti Aisyah; Hadma Yuliani; Luvia Ranggi Nastiti (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This service is carried out for the introduction of writing hijaiyah letters using card media. Community service carried out directly by researchers within one day at one of the Islamic education institutions, namely TK / TPA Nurul Ihsan Kalampangan. The use of card media helps in introducing and learning to write hijaiyah letters. Conducive environment and hands-on approach in learning contribute positively to children's creativity in understanding and writing hijaiyah letters. The use of hijaiyah letter card media can determine the ability to write in children, besides that it can also attract interest and motivation so that children are enthusiastic about learning. That way children are easy to do learning to write hijaiyah letters.